Use of Complementary and Alternative Medicine Among Newly Diagnosed Breast Cancer Patients in Malaysia: An Early Report From the MyBCC Study. (June 2018) - Zulkipli, Aina Farhana; Islam, Tania; Mohd Taib, Nur Aishah; Dahlui, Maznah; Bhoo-Pathy, Nirmala; Al-Sadat, Nabilla; Abdul Majid, Hazreen; Hussain, Samsinah
Background. The use of complementary and alternative medicine (CAM) has increased and little is known on CAM use during the initial period. Therefore, the aim was to determine prevalence of CAM use among newly diagnosed breast cancer patients prior to seeking conventional treatment. Methods. This is a cross-sectional study involved interviewing newly diagnosed breast cancer patients in the University Malaya Medical Centre (UMMC) using a structured questionnaire. Eligible respondents were interviewedduring a routine clinical visit. Results. A total of 400 patients were interviewed, of whom 139 (34.8%) were CAM users. Dietary supplementation (n = 107, 77.0%) was the most frequently used type of CAM, followed by spiritual healing (n = 40, 28.8%) and traditional Chinese medicine (n = 32, 23.0%). Malay ethnic group (n = 61, 43.9%) was the largest group of CAM users, followed by Chinese (n = 57, 41.0%) and Indian (n = 20, 14.4%). Majority of these CAM users (n = 87, 73.1%) did not disclose the use of CAM to their doctors. Most of them used remedies based on the recommendation of family and friends. Malay ethnicity and patients with 3 or more comorbidities were more likely to use CAM. Conclusion. There is substantial use of CAM among breast cancer patients in UMMC prior to seeking hospital treatment, and the most popular CAM modality is dietary supplements. Since, the majority of CAM users do not disclose the use of CAM to their physicians, therefore health care providers should ensure that those patients who are likely to use CAM are appropriately counseled and advised.